2015
DOI: 10.1111/luts.12091
|View full text |Cite
|
Sign up to set email alerts
|

Urodynamic Efficacy and Safety of Mirabegron Add‐on Treatment with Tamsulosin for Japanese Male Patients with Overactive Bladder

Abstract: Mirabegron add-on treatment with tamsulosin has efficacy and safety because it improves storage symptom without impairment of bladder contractility during voiding in male patients with OAB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
22
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 19 publications
5
22
1
Order By: Relevance
“…First, the impact of mirabegron on urodynamic parameters may be modest among those with MS and SCI. In uncontrolled studies in the overactive bladder population DO resolved in approximately 25-40% 25,26 ; we did not see a large proportion NDO resolve in our study, and this was not reported in in Krhut's study. Second, mirabegron appears to be an effective tool for improving symptoms among MS and SCI patients, similar to Krhut's study.…”
Section: Discussioncontrasting
confidence: 64%
“…First, the impact of mirabegron on urodynamic parameters may be modest among those with MS and SCI. In uncontrolled studies in the overactive bladder population DO resolved in approximately 25-40% 25,26 ; we did not see a large proportion NDO resolve in our study, and this was not reported in in Krhut's study. Second, mirabegron appears to be an effective tool for improving symptoms among MS and SCI patients, similar to Krhut's study.…”
Section: Discussioncontrasting
confidence: 64%
“…Several studies regarding mirabegron for patients with lower urinary tract symptoms accompanied by bladder outlet obstruction or BPH have been reported. For example, urodynamic studies involving men with lower urinary tract obstruction demonstrated that mirabegron treatment was non‐inferior to placebo in maximum urinary flow rate (Qmax) and detrusor pressure at Qmax (Pdet Qmax) while no effects on post‐void residual volume (PVR), Qmax and PdetQmax were reported for Japanese men with persistent OAB symptoms receiving mirabegron add‐on therapy after tamsulosin treatment . However, in a study of mirabegron add‐on therapy to tamsulosin for treatment of OAB systems in men with benign prostatic obstruction, Ichihara and colleagues reported a significant increase in PVR at end of treatment in the tamsulosin and mirabegron combination group compared with the tamsulosin monotherapy group .…”
Section: Discussionmentioning
confidence: 99%
“…Several prior studies reported that the add‐on of an antimuscarinic or β3‐AR agonist to α1‐blocker therapy was effective for the treatment of persistent storage symptoms . For instance, the NEPTUNE and ASSIST studies assessed the efficacy of adding solifenacin to tamsulosin monotherapy for men with residual OAB symptoms .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the incidence of adverse effects, including constipation and dry mouth, is lower for β3‐AR agonists than it is for anticholinergic agents. Recently, several studies demonstrated that add‐on treatment with mirabegron for patients with residual OAB symptoms despite α1‐blocker monotherapy was more effective and safer than continuing α1‐blocker monotherapy …”
Section: Introductionmentioning
confidence: 99%